Pengaruh Kualitas Pelayanan, Kepercayaan Dan Harga Terhadap Kepuasan Pelanggan Maiden Barberrock (Studi Kasus Pada Maiden Barberrock Di Cabang Galaxy) - Novandra, Muhammad Fauzan; Suparman, Suparman (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to find out and analyze how much influence Service Quality, Customer Trust and Price partially or simultaneously have on Customer Satisfaction at Maiden Barberrock Galaxy branch in 2023. This research is a quantitative research with a cross sectional survey design approach. The population used in this research is Maiden Barberrock consumers in 2023 in 1 month with a population of 300 people. Based on Arikunto opinion (2010:112), the number of samples was taken from 20% of the population, namely 60 people. Sample selection was carried out using probability sampling with simple random sampling techniques. Quantitative data obtained from distributing questionnaires was analyzed using SPSS version 26 software.  The t test results show that there is an influence of Service Quality on Customer Satisfaction, where the significance value is 0.005 < 0.05, while the t value is 2,923 or > t table is 2.002. There is no influence of Trust on Customer Satisfaction, where the significance value is 0.965 > 0.05, while the t value is 0.044 or < t table of 2.002. There is an influence of price on customer satisfaction, where the significance value is 0.024 < 0.05, while the t value is 2,327 or > t table is 2.002. Meanwhile, the results of the F test show that there is a simultaneous influence of Service Quality, Trust and Price on Customer Satisfaction, where the Significance value is 0.000 < 0.05, while the Fcount value is 16,861 or > Ftable of 3.15. Meanwhile, based on the coefficient of determination (R Square), Service Quality, Trust and Price influence simultaneously (simultaneously) on Customer Satisfaction by 47.50%, while the remaining 52.50% is influenced by other variables not examined in the model or this equation.